Reversible acetylation of Hpo regulates the Hippo pathway - Fengyun Lei; Yan Ding; Yanyun Liu; Hongtan Li; Dafa Zhou; Wenhao Ding; Bin Liu; Xiaohan Sun; Xiaopei Wang; Yunhe Zhao; Qing-Xin Liu; Zizhang Zhou (Proceedings of the National Academy of Sciences, 2026)
The Hippo pathway, which is highly conserved from Drosophila to mammals, plays a crucial role in regulating organ size and tissue homeostasis. Dysregulation of this pathway has been linked to various diseases, including tumors. The pathway controls the subcellular localization of the transcription coactivator Yki through core kinases Hpo and Wts, ultimately influencing the expression of target genes. Extensive studies have shown that most components in this pathway undergo posttranslational modifications, such as phosphorylation and ubiquitination. Nevertheless, the role of acetylation in Hippo signaling is still not fully understood. In this study, we find that Hpo is subject to reversible acetylation by Nej and Hdac3, thereby regulating its stability. Loss of Hdac3 leads to an increase in the expression of Hippo target genes, which is completely rescued by overexpressing Wts, positioning Hdac3 upstream of Wts. Although Hdac3 localizes in both the cell cytoplasm and nucleus, only the cytoplasmic Hdac3 is involved in regulating the Hippo pathway, where it interacts with Hpo to deacetylate and stabilize it. Additionally, knockdown of the acetyltransferase Nej decreases the expression of Hippo target genes, a phenotype that can be reversed by simultaneously silencing Hdac3. Taken together, these findings shed light on the role of reversible acetylation in controlling the Hippo pathway and provide insights into growth regulation and potential therapeutic approaches for related diseases.